Shariah governance practices and regulatory problems of Islamic insurance companies in Bangladesh - Alam, Md. Kausar; Ab Rahman, Suhaimi; Hossain, Md Shamim; Hosen, Sharif (Human Resource Management Academic Research Society, 2019)
This paper aims to explore the current practices and problems in the Shariah governance framework of Islamic insurance in Bangladesh. The study reveals that the governance system of Islamic insurance companies in Bangladesh is largely based on voluntary initiatives by itself and there is an absence of full-fledged Shariah governance framework. All Islamic insurance companies in Bangladesh have their own SSB who performs the Shariah audits and review activities. Based on the critical review, it provides some suggestions for the improvement of the Shariah governance framework of Islamic insurance. In order to improve the Shariah governance system of Islamic insurance companies, Bangladesh government should enact a law for its operations and rulings. Moreover, the Insurance Development and Regulatory Authority of Bangladesh (IDRA) should improve its guidelines for Islamic insurance operations to comply with Shariah principles and may recognize the Central Shariah Council for Islamic Insurance of Bangladesh (CSCIIB) so that, they can supervise and monitor the overall activities of Islamic insurance companies in Bangladesh.